Poster 120: The impact of the COVID-19 pandemic on injury onset and timing in Division 1 NCAA athletes - Wu, S.; Upfill-Brown, A.; Bugarin, A.; Jones, K.; Kremen, T.; Shi, B. (Orthopaedic Journal of Sports Medicine, 2022)
Objectives: The spread of the coronavirus disease 2019 (COVID-19) in February and March of 2020 led to the delay or cancellation of major sporting leagues and events across the globe. Collegiate athletic competitions were postponed until the end of the 2020 calendar year and organized collegiate athletic practices and training camps throughout 2020 were either cancelled or significantly reduced in frequency. The impact of the COVID-19 pandemic on injury epidemiology in collegiate athletics has not yet been investigated. We aim to describe the types of athletic injuries sustained by high level collegiate athletes before and after the COVID-19 pandemic. Methods: The Pacific 12 (Pac-12) Health Analytics Program contains all injuries sustained by intercollegiate athletes in the Pac-12 conference. This database was queried for injuries that occurred across all sports from January 2019 to June 2021. For all sports, timing of injury onset (acute versus overuse), severity of injury, rate of procedural intervention, injury mechanism (contact versus non-contact), and likelihood of injury during the 4th quarter of competition (final 25% of competition) was compared between the season immediately preceding the COVID-19 pandemic and the season immediately after. In this database, injury timing is defined as overuse if symptom onset occurred more than 24 hours after the precipitating incident. Results were stratified by upper and lower extremity as well as sport. Sub group analyses were also performed on knee and shoulder injuries among athletes competing in sports with historically high rates of knee and shoulder injuries. Multivariate analysis including gender was performed. Results: A total of 12,319 sport-related injuries across 23 sports were identified. The overall proportion of injuries sustained during the 4th quarter of competition was higher in the post-pandemic season (28.5% vs. 25.9%, p=0.015) and the overall proportion of non-contact injury was higher in the post-pandemic season (46.1% vs. 39.8%, p<0.0001). These findings were replicated when stratifying by upper and lower extremity injury. In sports with traditionally high rates of knee injuries (football, soccer, basketball, lacrosse, gymnastics), there was a higher proportion of overuse knee injuries (21.2% vs. 14.5%, p=0.003) and a higher proportion of non-contact knee injuries (47.6% vs 37.4%, p<0.0001) sustained in the post-pandemic season. In sports with high rates of shoulder injuries (football, baseball, softball, gymnastics, swimming, volleyball), there was a higher proportion of shoulder injuries taking place in the final 25% of competition (27.2% vs. 18.8%, p=0.016)) and a higher proportion of non-contact shoulder injuries (37.6% vs. 24.9%, p<0.0001) sustained in the post-pandemic season. Multivariate analysis also demonstrated higher rates of non-contact (OR 1.28, p<0.0001) and overuse injuries (OR 1.30, p=0.001) observed in the post-pandemic season and showed that female gender was significantly associated with overuse injury (OR 1.92, p<0.0001), non-contact injury (OR 1.35, p<0.0001), season ending injury (OR 2.33, p=0.008), and decreased likelihood of procedural intervention (OR 0.55, p<0.0001). Conclusions: Compared with the season immediately preceding the COVID-19 pandemic, athletes competing in the post-pandemic season were at higher risk of non-contact injury and injury near the end of a competition. There was a higher risk of overuse knee injuries and non-contact knee and shoulder injuries in the post-pandemic season. These findings are the first to describe the effect of a global pandemic on an athlete`s injury risk profile upon return to sport and may be used to guide decisions regarding athlete workload and training.